First trimester antenatal care contact in Africa: a systematic review and meta-analysis of prevalence and contributing factors - Ritbano Abdo; Minychil Demelash; Abdulrezak Mohammed Seid; Abdulhakim Mussema (BMC, 2023)
Abstract Background Early detection, prevention, and management of diseases associated with pregnancy and pregnancy-related conditions depend on the beginning of antenatal care contact in the first trimester. Across Africa, regional and national differences are observed in the proportion of first-trimester ANC contact and the factors contributing to it. To create a suitable intervention plan, it is crucial to overcome these differences through single standard and uniform guidelines. This can be achieved through meta-analysis and systematic reviews. Therefore, this systematic review aimed to assess the pooled prevalence of first trimester ANC contact and the factors contributing to it in Africa. Methods Observational studies conducted in Africa were retrieved from PubMed, Google Scholar, EMASE, CINHAL, Cochrane Library, Hinari databases and Mednar using combinations of search terms with Boolean operators. The JBI 2020 Critical Appraisal Checklist was used to assess the methodological quality of the studies. To assess publication bias, a funnel plot and Egger's test were used to and I-squared was used to check the heterogeneity of the included studies. Data were extracted using Microsoft Excel and exported to Stata 16 software for analysis. Results A total of 86 articles with 224,317 study participants from 19 African countries were included. The overall pooled prevalence of first-trimester ANC contact was 37.15% (95% CI: 33.3-41.0; I2 = 99.8%). The following factors were found to be significantly associated with first-trimester ANC contact: urban residence (OR = 2.2; 95% CI: 1.5-3.1; I2 = 98.5%); women under the age of 25 (OR = 1.5; 95% CI: 1.2-1.9; I2 = 94.1%);, educational status (OR = 1.8; 95% CI: 1.4-2.2; I2 = 96.1%), primiparity (OR: 1.7; 95% CI: 1.2-2.4: I2 = 97.4%), having planned pregnancies (OR: 2.1; 95% CI: 1.5-2.7; I2 = 95.5%) and employed women (OR = 1.7; 95% CI: 1.7-2.1; I2 = 94.4%). Conclusion Because so few women in Africa initiate first-trimester ANC contact, it is clear that increasing maternal healthcare service uptake is still a challenge and will require significant effort to scale up the services. When working to improve maternal health in Africa, each nation's government and nongovernmental organizations should prioritize raising women's educational levels and providing pertinent information to rural women, focusing on reducing unintended pregnancies, women who live far from health facilities, women with low socioeconomic statuses, multiparous women and older women. Trial registration PROSPERO International Prospective Register of Systematic reviews (ID: CRD42023401711).